An Inquiry into the Nature and Causes of the Happiness of Nations - Nicholas, Ryan Ralph (Philippine Social Sciences Review; PSSR Vol. 69 No. 2 2017, Ed. Rogelio Alicor L. Panao, 2018)
Authoritarian rulers and their supporters often argue that limiting freedom is necessary to attain and preserve economic development in the interest of the country’s welfare and the citizens’ well-being. If happiness is the ultimate pursuit of human beings in life, then what makes nations happy? Does freedom bring happiness? To answer this question, I analyzed the happiness of nations based on the Cantril scale of the World Happiness Report, along with other socioeconomic and political variables in 116 states. Controlling for economic development, unemployment, inequality, corruption, democracy, and life expectancy, OLS estimates suggest that freedom causes happiness only in countries where it is culturally important. Ultimately, albeit rather surprisingly, the results reveal that economic development remains to be the most important universal determinant of happiness.
Keywords: Cantril scale, cultural relativism, economic development, freedom, happiness